Alloreactive T Cells Display a Distinct Chemokine Profile in Response to Conditioning in Xenogeneic GVHD Models. Issue 9 (September 2019) - Kawasaki, Yasufumi; Sato, Kazuya; Nakano, Hirofumi; Hayakawa, Hiroko; Izawa, Junko; Takayama, Norihito; Mashima, Kiyomi; Oh, Iekuni; Minakata, Daisuke; Yamasaki, Ryoko; Morita, Kaoru; Ashizawa, Masahiro; et al.
Abstract : Background: Chemokines and chemokine receptors are potential targets for the prevention and treatment of graft-versus-host disease (GVHD). The objective of the current study is to determine the clinical relevance of xenogeneic transplantation models in terms of host and donor chemokine profiles and, if this is the case, to assess the clinical efficacy of C–C chemokine receptor (CCR) 5 antagonist maraviroc for the prevention of GVHD using this model. Methods: Xenogeneic GVHD was induced by intravenous injection of 5 × 10 6 human pan T cells into NOD/Shi-scid-IL2rγ null (NOG) mice or MHC class I/II-deficient NOG mice in the presence or absence of total body irradiation before transplantation. Results: Extensive tissue destruction with human T-cell infiltration was observed throughout the body, particularly in lungs and liver, but relatively mild in gut. Consistent with this finding, quantitative polymerase chain reaction confirmed the upregulation of mouse CXC chemokine ligand (CXCL) 9 and CXCL10 in lungs and CCL4 in lungs and liver but not in gut. The addition of total body irradiation (1) led to the early release of mouse CCL4 and CXCL10, (2) upregulated a number of chemokine-related genes in human T cells, (3) induced higher expression of CCR5 on human CD4 + and CD8 + T cells and CXCR3 on human CD4 + T cells, and (4) promoted their migration and proliferation in organs, resulting in more severe tissue damage. In this context, pharmacological CCR5 blockade neither ameliorated GVHD nor prolonged survival in NOG mice. Conclusions: Our experimental data do not demonstrate clinical benefit of CCR5 antagonist for the prevention of GVHD in a myeloablative setting. Abstract : Supplemental Digital Content is available in the text.